The social accounting matrix and the socio-demographic matrix-based approaches for studying the socioeconomics of ageing - Santos, Susana (2016)
In looking for empirical evidence about the activity of countries, a proposal is made for studying (measuring and modelling) the activity of countries through the use of Social Accounting Matrices (SAMs) and Socio-Demographic Matrices (SDMs). SAMs and SDMs are presented as tools that have specific features for conducting studies in several different areas, particularly in the Socio-Economics of Ageing, as well as for supporting policy decision processes. Based on methodological principles that are derived mainly from the works of Richard Stone, emphasis is placed on the desirability of working in a matrix format, which includes not only people (SDM), but also, at the same time, activities, products, factors of production and institutions (SAM). This is considered to be a way of capturing the relevant network of linkages and the corresponding multiplier effects for the subsequent modelling of the activity of the countries studied. The exposition of this proposal is accompanied by an example applied to Portugal.